Virtual Reality: Is It Real Or Not? - S. Serap Kurbanoğlu (Türk Kütüphaneciliği)
In this paper virtual reality technology and how libraries might be affected by this technology are examined. Virtual reality sets out to address a problem. The problem is that of user-friendliness of computer systems. Needless to say, the current generation of computers still involves a barrier between human and machine. This is keyboard or mouse on the human side, and the screen on the computer side. If computers are really going to become a part of everyone’s normal day to day experiences, they, must allow users to visualise information in a way familiar to them, not the way the computers forces them to. Virtual reality provides such a way. With the increasing amounts of information available in electronic form, it is clear that virtual reality technology will have a profound impact on libraries.